THYROID CANCER RISK ATTRIBUTABLE TO THORAX COMPUTED TOMOGRAPHY (CT) EXAMINATION - Iza Nurzawani Che Isa; Lim Jia Hui; Thilageswary A/P Veerasingam (Journal of Islamic, Social, Economics and Development, 2021)
This study was carried out to determine the radiation dose to thyroid and effective lifetime risk of radiation-induced thyroid cancer from thorax CT examination. The risk of radiation-induced thyroid cancer due to thorax CT examination is very much present and should not be ignored. A total of 2168 set data of CT dose parameters for thorax CT examinations were obtained retrospectively and analysed using CT-Expo and WAZA-ARI to get the absorbed dose to thyroid organ. The dose to thyroid organ ranged from 7.95 mGy to 14.18 mGy for HRCT examinations and 14.40 mGy to 16.99 mGy for TAP examinations. The organ doses were found to vary within the two analytical software packages. The effective lifetime risk was calculated by multiplying equivalent dose and lifetime attributable risk (LAR) based on Biological Effects in Ionizing Radiation (BEIR) Report VII. The demographic factor and the effective risk of thyroid cancer were analyzed. Generally, there were significant differences in the estimated risk among between gender, age and ethnic groups. The estimated risk for females was shown to have a higher mean rank compared to male. Older people tended to have lower cancer risk compared to other age groups. Malays appeared to have a higher risk, followed by Indian and then Chinese. The effective cancer risk of radiation-induced thyroid cancer through thorax CT examination may be low but it is, nevertheless, important. Optimization protocols should not be ignored in the role of reducing radiation thyroid cancer risk to patients.